FRI0178 PREDICTIVE FACTORS FOR POOR SLEEP QUALITY IN SYSTEMIC LUPUS ERYTHEMATOSUS. (2nd June 2020) - Magro, R.; Camilleri, L.; Borg, A.
Abstract : Background: Poor sleep quality is common in systemic lupus erythematosus (SLE) and could contribute to fatigue, which is regarded as one of the most disabling symptoms in SLE. The Pittsburgh sleep quality index (PSQI) is a validated self-administered questionnaire that measures sleep quality over the previous month. 1 Objectives: The aim of this study was to analyse the relationship of sleep quality with several variables including depression, anxiety, pain, disease activity, fatigue and functional disability in patients with SLE. A further aim was to establish the prevalence of poor sleep quality in SLE. Methods: A cohort cross-sectional study was carried out including 92 SLE patients who fulfilled the SLICC classification criteria for SLE and who provided informed consent for participation. The patients were interviewed and they were asked to fill in questionnaires including PSQI, Fatigue Severity Scale (FSS), Hospital Anxiety and Depression Scale (HADS), visual analogue scale (VAS) for pain and modified Health Assessment Questionnaire (mHAQ). Blood and urine tests enabled the calculation of SLE disease activity index-2K (SLEDAI-2K). The study was approved by the University Research Ethics Committee. Results: 92.4% of the cohort studied were females, and the mean age was 46.9 years (range 19-79 years). 55.4% were noted to have poor quality sleep (PSQI >5), and the median PSQI was 6 (range 0-18). Sleep quality measured by PSQI, had a significant correlation with SLEDAI-2K (R=0.254, p=0.014), VAS pain (R=0.515, p<0.001), HADS-D (R=0.605, p<0.001), HADS-A (R=0.375, p<0.001), estimated glomerular filtration rate (eGFR) (R=-0.211, p=0.044), FSS (R=0.551, p<0.001) and mHAQ (R=0.559, p<0.001). ANCOVA analysis showed that PSQI was significantly dependant on VAS pain (p<0.001), HADS-D (p<0.001) and eGFR (p=0.003). Conclusion: Poor sleep quality is highly prevalent in SLE patients. This study has shown that the strongest predictive factors for poor sleep quality are pain, depression and impaired renal function. Since poor sleep quality is significantly related to fatigue and functional disability, its identification and management is important for patients' wellbeing. References: [1]Buysse DJ, Reynolds CF 3rd, Monk TH, Berman SR, Kupfer DJ. The Pittsburgh Sleep Quality Index: a new instrument for psychiatric practice and research. Psychiatry Res. 1989; 28: 193 – 213. Disclosure of Interests: None declared